Respon Anatomis Jagung (Zea mays L.) ‘Sweet Boy-02’ pada Perbedaan Intensitas Cahaya dan Penyiraman - Hafidha Asni Akmalia; E. Suharyanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
The difference of environmental condition makes the change of anatomical structure related to its growth. This phenomenon gives an information about maize’s adaptation. The aims of the research was to evaluate anatomical response of maize in different light and water treatment. This research used Randomized Completed Design with 3 regimes of light intensity ( L1 (63694); L2 (11408); L3(3897) Lux) and 3 regimes of watering (2 L/ 1,6 L/ and 1,2 L). Each combination was done with 3 replications. Maize was harvested in 75 days after treatment and the parts of plant including leaf, stem, and root were preserved using paraffin embedding method. The measured anatomical responses were leaf thickness; stomatal indeks; root and stem tracheal diameter. Data were analyzed by Anava and DMRT test with significance level of 5%. The results showed that the light intensity L1(63694 Lux) and watering W1(2 L) caused thicker leaf, the larger stomatal index and root’s tracheal diameter. The leaf thickness was 368,67 µm, stomatal index was 31,37 %, and root’s tracheal diameter was 176,10 µm in L1W1 treatment showing the value was the largest and different significantly than the other treatments. While, the stem’s tracheal diameter was not significant because the stem was the last part of plant affected by the treatment. Keywords : maize, Sweet Boy-02, anatomical response, adaptation.